STUDI EKSPERIMENTAL KUAT TEKAN BETON YANG MENGGUNAKAN SILICA FUME SEBAGAI PENGGANTI 10% DARI BERAT SEMEN PORTLAND TIPE I DENGAN VARIASI MEDIA PERENDAMAN - John Pattinasarany (Racic : Rab Construction Research, 2026)
Concrete structures located in coastal areas are highly vulnerable to deterioration due to exposure to the aggressive marine environment. The presence of chloride and sulfate ions in seawater can penetrate the concrete's pore structure, leading to a reduction in its mechanical strength. Therefore, the selection of an appropriate curing medium is a crucial factor in evaluating concrete durability under such conditions. This study aims to examine the effect of different curing media on the compressive strength of concrete modified with 10% silica fume as a partial replacement for Type I Portland cement. Cylindrical concrete specimens were immersed in three types of curing environments: fresh water, static seawater, and dynamic seawater (directly submerged in the ocean). Compressive strength tests were conducted at 14, 28, and 56 days of curing. The results indicate that the type of curing medium has a significant influence on the performance of the concrete. Specimens cured in fresh water exhibited the highest compressive strength across all curing ages. In contrast, concrete immersed in static seawater showed the lowest performance. Meanwhile, specimens cured in dynamic seawater performed better than those in static conditions but still fell short of the performance achieved with fresh water curing.